The Latin American economy during 1984: A preliminary overview - Enrique V. Iglesias (CEPAL Review, 1985)
As is customary, at the end of 1984 the Executive Secretary of ECLAC presented a review of developments in the Latin American economy during the past year, and the text of this review is reproduced in the present article.